Financial Strategy Based on Financial Performance Analysis of PT Bukit Uluwatu Villa during COVID-19 (The Indonesian Journal of Business Administration, 2021)
PT Bukit Uluwatu Villa Tbk is a provider of in accommodation services (cottages) and hospitality in Indonesian. They offer a luxury resort experience that is suitable for visitors who seek peace, comfort, and closeness to nature. The company strives to showcase the unique local culture as well as the green concept that characterizes the Company's properties. Three properties that have been operating for a long period of time; show a good reputational company and good brand name position in hospitality industry with several awards and achievement. The problem however is that they face demand loss due to impact of COVID-19 crisis which begin in 2020 and uncertain situation for demand recovery. This brings forth the urgency to monitor company financial performance during the period. To analyze and research company’s financial performance, financial ratio analysis is used in this research to gain information about the business situation that company will face. The primary data gathered is BUVA’s Annual Report between 2015 to 2019 and BUVA’s Financial report Q3/2020. The data analysis reveals company’s financial performance is in bad condition due to poor profitability ratio. Therefore, operational restructuring is recommended to optimize the company's profitability to save the company from a possible default in short term due to uncertainty situation caused by COVID- 19 crisis. Keywords: financial performance, financial ratio, profitability, dupont analysis, hospitality industry